Allelopathic potential of white cabbage on some plants - Leyla Kural; Reyyan Yergin Özkan (Plant, Soil and Environment, 2020)
The aim of this study carried out in 2017-2018 was to determine the effect of white cabbage (Brassica oleracea L.), which is known to have an allelopathic effect on the germination of some weed and cultural crops seeds. In addition to weeds, Amaranthus retroflexus L., Chenopodium album L. and Solanum nigrum L., cultural plants such as Zea mays L., Beta vulgaris L., were used in this study. It has been shown that the seed germination rate was decreased by the increased concentration of white cabbage post-harvest leaves extractions, which were made with different concentrations of aqueous and methanol extracts (30, 40, and 50%). The methanol extract was found to be more effective in germination. According to these results, S. nigrum and Z. mays seeds were less affected than A. retroflexus, C. album and B. vulgaris seeds. In the light of these data, it is observed that extracts obtained from white cabbage can be effective on some weeds; however, it was concluded that in order to reach more definite conclusions, studies on the subject should be increased, and similar studies should be continued under greenhouse or field conditions.